The Integration-Interconnection of Sciences in Early Islamic Historiography: A Study on Tārīkh al-Rusul wa al-Mulūk by al-Ṭabarī - Nurul Hak; Kholili Badriza (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
This article examines the integration-intercon-nection of sciences in Tārīkh al-Rusul wa al-Mulūk. It argues that the integration-interconnection has been an integral part of early Islamic historiographical works. Hence there were no historical problems related to the integration-interconnection in the treasures of Islamic sciences. This research employs the integration-inter-connection and the functional theory as a conceptual framework. This research also uses the historical method, comprising heuristic, data verification, interpretation, and historiography. To further examine the issues, it also employs the intertextual approach. The results of this study showed that the integration interconnection in Tārīkh al-Ṭabarī is correlated to scientific and metho-dological aspects. The scientific element referred to here is the coherence and interrelation among the subjects of history, literature, ‘Ulūm al-Qur’ān, and ‘Ulūm al-Ḥa-dīth in Tārīkh al-Ṭabarī. At the same time, the methodolo-gical aspect referred to the meaning, function and implication of the integration-interconnection, either in the study of Islamic history or Islam in general.